Body temperature measurement uncertainty arising from ear canal geometry and temperature gradients. (December 2022) - Alonso, Pablo Castro; Machin, Graham
Abstract: We report the results of a numerical thermal model of the ear canal and tympanic membrane. The model was used to assess the uncertainty contributions in determining body temperature arising from lower ear canal temperature gradients. We find that for reasonable assumptions of such gradients the standard uncertainty contribution is < 0.1 °C.